Ibigkas! 2.0: Directions for the Design of an Adaptive Mobile-Assisted Language Learning App - Rodrigo, Ma. Mercedes T (Archīum Ateneo, 2019)
Ibigkas! is a team-based mobile-assisted language learning application that provides students with English language practice. Working collaboratively rather than competitively, players must find the rhyme, synonym, or antonym of a given target word among different lists of words on their mobile phones. At this time, Ibigkas! is not adaptive. In order to anticipate the needs of an adaptive version of the game, we conducted a workshop in which students and teachers from the target demographic played the game and then participated in focus group discussions. Based on their feedback, we conclude that an adaptive version of the game should include metacognitive support and a scoring system that enables monitoring of individual performance based on individual mistakes or non-response. Tracking of individual performance will enable us to build in other articulated student and teacher preferences such as levelling up, rankings, adaptive difficulty level adjustment, and personalized post-game support.